Asymmetric investment responses to firm-specific forecast errors - Julian Berner; Manuel Buchholz; Lena Tonzer (Halle Institute for Economic Research (IWH), 2020)
This paper analyses how firm-specific forecast errors derived from survey data of German manufacturing firms over 2007-2011 affect firms' investment propensity. Understanding how forecast errors affect firm investment behaviour is key to mitigate economic downturns during and after crisis periods in which forecast errors tend to increase. Our findings reveal a negative impact of absolute forecast errors on investment. Strikingly, asymmetries arise depending on the size and direction of the forecast error. The investment propensity declines if the realised situation is worse than expected. However, firms do not adjust investment if the realised situation is better than expected suggesting that the uncertainty component of the forecast error counteracts positive effects of unexpectedly favorable business conditions. Given that the fraction of firms making positive forecast errors is higher after the peak of the recent financial crisis, this mechanism can be one explanation behind staggered economic growth and slow recovery following crises.
urn:nbn:de:gbv:3:2-120031
Keywords: D22; D84; E32; 330; risk climate; microeconomic survey data; forecast errors; firm investment; uncertainty